F09 Higher prevalence of Huntington's disease in South Korea. (12th September 2022) - Kim, Manho; Lee, Jee-Young
Abstract : Background and Aims: In Asian countries, incidences of Huntington's disease (HD) are lower than those of Western countries. Previous reports in South Korea were based on detection from hospitals. Incidence of general population is unknown. Methods: Health insurance has been covered by government in South Korea. This system enables the investigator to assess big data to identify patients' data with Huntington's disease. Database was between 2010 and 2019. Diagnosis of HD were confirmed by genetically. We compared the prevalence to previous ones in South Korea, and to those of other countries including Europe. Ten-year prevalence, mean age of onset at the time of diagnosis, including CAG repeats were described. Results: New HD patients (average N= 152.10) have been detected every year. Prevalence of HD is 2.22 per 100, 000 persons, higher than previous reports in South Korea. It is higher than those of Asian countries (0.40; CI: 0.26-0.61). Comparing to the pooled data from North America, Europe, and Australia, it is approximately half of the prevalence of 5.70 (CI: 4.42-7.35). The most common age at the time of diagnosis was the 6th decade (50-59 years; 23.3%) with CAG repeat dependent. Conclusion: The newly updated prevalence of HD is higher in South Korea. Further inclusion of missing patients (those without exposure to Korean National Insurance System; undiagnosed carriers/unawareness of HD) will likely increase the prevalence.